Design and Sensitivity of the Radio Neutrino Observatory in Greenland (RNO-G) - Aguilar, J. A.; Allison, P.; Connolly, A.; Dasgupta, P.; De Kockere, S.; De Vries, K. D.; Deaconu, C.; Duvernois, M. A.; Feigl, N.; García-Fernández, D.; Glaser, C.; Hallgren, A.; et al. (Journal of Instrumentation, 2021)
This article presents the design of the Radio Neutrino Observatory Greenland (RNO-G) and discusses its scientific prospects. Using an array of radio sensors, RNO-G seeks to measure neutrinos above 10 PeV by exploiting the Askaryan effect in neutrino-induced cascades in ice. We discuss the experimental considerations that drive the design of RNO-G, present first measurements of the hardware that is to be deployed and discuss the projected sensitivity of the instrument. RNO-G will be the first production-scale radio detector for in-ice neutrino signals.